The effects of 2,4-Dichlorophenoxyacetic Acid on the induction of callus from cotyledon and hypocotyl explants of Butterfly Pea (Clitoria ternatea) - Siew, Chin Teoh; Sreeramanan Subramaniam,; Bee, Lynn Chew (Penerbit Universiti Kebangsaan Malaysia, 2023)
Clitoria ternatea (Butterfly pea) is a tropical medicinal and fodder legume from the Fabaceae family possessing various beneficial phytochemical compounds linked to the mammalian neuroprotective mechanism. Callus and cell suspension cultures are excellent alternatives for harnessing secondary metabolites from medicinal plants. The current study aims to induce callus from cotyledon and hypocotyl explants of C. ternatea for the establishment of cell suspension cultures. Cotyledon and hypocotyl explants from two-weeks-old seedlings were subjected to half-strength MS medium supplemented with 2,4-dichlorophenoxyacetic acid (2,4-D) at different concentrations (0.5 mg/L to 2.5 mg/L) and callus scoring and morphology were assessed at week 8 of culture. Results revealed that the treatment of 0.5 mg/L 2,4-D resulted in the highest percentage of callus induction (100%) and the highest callus scoring for both cotyledon and hypocotyl explants with friable callus morphology. Cotyledon explants exhibited a higher callus scoring with a relative value of 3.03 ± 0.20 compared to hypocotyl explants at 1.80 ± 0.12. This study thereby provides a basis for future studies on callus induction studies and the establishment of cell suspension cultures of C. ternatea for the production of valuable secondary metabolites linked to the memory enhancing properties of the plant.